Breeding management practices of dairy animals followed by farmers in Valsad district of Gujarat (Indian Journal of Animal Production and Management, 2024)
A field survey was conducted to ascertain the breeding management practices followed by dairy animals owners in Valsad district of Gujarat and data were collected from randomly selected 240 respondents from two talukas through personal interview with the help of structured interview schedule. The present study revealed that all the respondents detected heat in their animals by observing the symptom of mucus discharge (67.90 %) and bred their animals by artificial insemination (98.93 %) during mid-heat after heat detection (70 %). About 76.27 % respondents bred their animals after 3-5 months of calving and 89.20 % respondents followed the pregnancy diagnosis by livestock inspector after three months of breeding. Majority (91.20 %) of the respondents followed treatment of anestrous/repeaters in their dairy herds and only 3.80 % of the respondents kept the breeding records of their dairy animals.
Keywords: Animals; Breeding; Dairy; Management; Pregnancy